Visualization study on vortex structure over an airfoil using planar laser induced fluorescence. Issue 7 (9th August 2018) - Chang, Guang; Peng, Jiangbo; Yu, Xin; Dong, Hao; Deng, Fan; Chen, Lin; Fan, Rongwei; Dong, Zhiwei; Li, Xudong
Abstract: The research discussed the application of planar laser-induced fluorescence technique for visualizing the flow over an airfoil at different Reynolds numbers and angles of attack. The proposed arrangement allows visualizing the development process of the flow field structure around the airfoil. The focus of the study is the influence of the angles of attack and the Reynolds number on the separation boundary layer, which causes the wake vortex or separation bubble. Compared with the traditional visualization technology, the technology of planar laser-induced fluorescence has better time resolution (50 ns) and followability (Reynolds number = 219, 500). In order to achieve high-speed flow field visualization, planar laser-induced fluorescence provides a reliable means of measurement to solve the related engineering problems.